Xerostomia: The Causes and Clinical Management Including Acupuncture and Herbal Medicine - Zhao, Min (Archives of Clinical and Medical Case Reports, 2022)
Background: Xerostomia is chronic sensation of a dry mouth and affects a large part of the population. Xerostomia often severely impairs quality of life with patients experiencing tooth caries, altered taste and smell, difficulty talking, problems with chewing, burning tongue, candida infection and so on. The pathology and course of xerostomia are not well described, many factors could cause xerostomia. It is usually the complex reasons for patients with xerostomia and identifying the causes will help guide clinical management. Several therapeutic strategies are available for xerostomia. However, these treatments achieve limited effects and often induce adverse effects. Main Body of the Abstract: This review focus on the causes and clinical management of xerostomia, including acupuncture and herbal medicine. Short Conclusion: The complementary and alternative medicine such as acupuncture and herbal medicine could be helpful in patients suffering from xerostomia.